THE INFLUENCE OF RELIGIOUS BELIEFS ON MORAL DECISION-MAKING: A DUAL PROCESS PERSPECTIVE - Khasanova Dilbar (Web of Journals Publishing, 2024)
This article investigates the relationship between religious beliefs and moral decision-making, focusing on sacrificial moral dilemmas where individuals must weigh the value of causing harm to achieve a greater good. Drawing on the dual process model of moral judgment, we explore how intuitive and reflective processes contribute to the tendency of religious individuals to prioritize deontological principles over utilitarian outcomes. While prior research has predominantly associated religious adherence with intuitive processing and deontological moral reasoning, recent studies suggest a more nuanced understanding may be necessary. Reflective thinking among religious individuals may not only reinforce deontological norms but also serve impression management concerns and enhance perceptions of moral character. Consequently, the interplay between intuitive and reflective processes may offer insights into the complexities of moral decision-making among religious and non-religious individuals alike.